2020
DOI: 10.1101/2020.08.26.20182618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-COVID-19 Functional Status: Relation to age, smoking, hospitalization and comorbidities

Abstract: Rational: Recently, a new Post-COVID-19 Functional Status (PCFS) scale is recommended in the current COVID-19 pandemic. It is proposed that it could be used to display direct retrieval and the functional sequelae of COVID-19. Aim of the study: To assess the Post COVID-19 functional status in Egypt and to evaluate if age, gender, comorbidities have any effect on functional limitations in recovered COVID-19 patients. Patients and methods: A total of 444 registered confirmed COVID-19 patients were included. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Male patients make up 57.4% of the total population, with female patients making up the remaining 42.6%. These results were in line with some earlier research and global trends 6,[13][14][15] which represented both developed and developing nations. The study also sheds light on the diverse socio-economic backgrounds of COVID-19 survivors, revealing that a majority, or 56.6%, were employed individuals, and a substantial 82% had attained an education level beyond secondary school.…”
Section: Discussionsupporting
confidence: 92%
“…Male patients make up 57.4% of the total population, with female patients making up the remaining 42.6%. These results were in line with some earlier research and global trends 6,[13][14][15] which represented both developed and developing nations. The study also sheds light on the diverse socio-economic backgrounds of COVID-19 survivors, revealing that a majority, or 56.6%, were employed individuals, and a substantial 82% had attained an education level beyond secondary school.…”
Section: Discussionsupporting
confidence: 92%
“…Two prospective and two retrospective cohort studies as well as three cross-sectional studies were grouped under the term “general health” [ [7] , [8] , [9] , [10] , [11] , [12] , [13] ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study reported functional restrictions (e.g. changes in life-style, sports and social activities) in 80% of participants, albeit 63% thereof was considered negligible [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…84 However symptom duration, patient populations, and length of follow-up are highly variable between studies, with reported rates of full recovery between 13% and 86% at follow-up ranging from 30 to 186 days (Table 2). 7173,75,78,83,85103…”
Section: Covid-19 and Me/cfsmentioning
confidence: 99%
“…84 However symptom duration, patient populations, and length of follow-up are highly variable between studies, with reported rates of full recovery between 13% and 86% at follow-up ranging from 30 to 186 days (Table 2). [71][72][73]75,78,83,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103] An observational study investigating post-acute COVID-19 symptoms as defined by ME/CFS criteria does not yet exist. However, the high prevalence of persistent fatigue is very relevant to ME/ CFS.…”
Section: Covid-19 and Me/cfsmentioning
confidence: 99%